THE INFLUENCE OF LOAN TO DEPOSIT RATIO, EFFECTIVE TAX RATE AND NON-PERFORMING LOAN TOWARD RETURN ON ASSET IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ciptawan, Ciptawan; Melly, Melly (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2022)
Bank is an intermediary institution in charge of receiving deposits from customers and lending them to customers (economic units) who need funds. One of the main activities of banks is to channel funds to the public in the form of credit. The bank will need to pay attention to the Loan to Deposit Ratio to secure its liquidity, effective tax rate as the tax planning to secure the tax paid and Non-Performing Loan to control the bad debt. The bank will need all the variables to control the Return on Assets. The research result showed that partially Loan to Deposit Ratio (LDR) has no influence toward Return on Asset, Effective Tax Rate (ETR) has negative influence toward Return on Asset, Non Performing Loan (NPL) has negative influence toward Return on Asset. Simultaneously hypothesis showed that Loan to Deposit Ratio, Effective Tax Rate and Non Performing Loan have effect toward Return on Asset.